1997
DOI: 10.1111/j.1432-1033.1997.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavin Adenine Dinucleotide and Flavin Mononucleotide Metabolism in Rat Liver

Abstract: In order to gain some insight into mitochondrial flavin biochemistry, rat liver mitochondria essentially free of lysosomal and microsomal contamination were prepared and their capability to metabolise externally added and endogenous FAD and FMN tested both spectroscopically and via HPLC.The existence of two novel mitochondrial enzymes, namely FAD pyrophosphatase (EC 3.6.1.18) and FMN phosphohydrolase (EC 3.1.3.2), which catalyse FAD+FMN and FMN-riboflavin conversion, respectively, is shown. They differ from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 41 publications
5
65
2
Order By: Relevance
“…Evidence in support of this study is provided by the observation obtained by Daniel et al 12) that both degradative enzymes, FAD pyrophosphatase and FMN phosphatase, from intestinal mucosa were also inhibited in vitro by EDTA. Inhibition studies with AMP (1 mM), a known inhibitor of mitochondrial FAD pyrophosphatase, 9) yielded similar result. The residual percentage of FAD was 96.7Ϯ1.5% at 30 min at 4°C.…”
Section: Hydrolysis Of Fad In Rat and Human Plasmasupporting
confidence: 62%
See 1 more Smart Citation
“…Evidence in support of this study is provided by the observation obtained by Daniel et al 12) that both degradative enzymes, FAD pyrophosphatase and FMN phosphatase, from intestinal mucosa were also inhibited in vitro by EDTA. Inhibition studies with AMP (1 mM), a known inhibitor of mitochondrial FAD pyrophosphatase, 9) yielded similar result. The residual percentage of FAD was 96.7Ϯ1.5% at 30 min at 4°C.…”
Section: Hydrolysis Of Fad In Rat and Human Plasmasupporting
confidence: 62%
“…2,9) The existence of two major enzymes, namely FAD pyrophosphatase and FMN phosphatase, which catalyze the conversion of FAD to FMN and the conversion of FMN to RF, respectively, is shown in mammals. [9][10][11] Figure 1c depicts the effect of EDTA on the hydrolysis of FAD and FMN in rat and human plasma at 4°C. Hydrolysis activity of FAD was strongly inhibited by EDTA, which is known as an anticoagulant, in plasma.…”
Section: Hydrolysis Of Fad In Rat and Human Plasmamentioning
confidence: 99%
“…Mitochondria were isolated from the liver of male Wistar rats (1502 00 g) and puri¢ed as reported in [11]. showing a respiratory control index lower than three were discarded.…”
Section: Methodsmentioning
confidence: 99%
“…showing a respiratory control index lower than three were discarded. Mitoplasts were obtained from puri¢ed RLM according to [11]. Mitochondrial protein was determined according to Waddel and Hill [12].…”
Section: Methodsmentioning
confidence: 99%
“…The broad pH profile for enzyme activity is consistent with a solvent-derived hydroxide ion nucleophile for which we have structural evidence in a substrate complex with FAD. There are reports of this enzyme activity associated with plant chloroplasts and mitochondria (49), yeast mitochondria (50), rat liver mitochondria (51), and human mitochondria (52)(53)(54). It has been reported that purified 5Ј-nucleotidase from human placental mitochondria possesses metal-dependent FAD pyrophosphatase activity (53), which is inhibited by EDTA and stimulated by Co 2ϩ and to a lesser degree by Mn 2ϩ .…”
Section: Tp0796 Inhibitor Complex (Adp-mg 2ϩmentioning
confidence: 99%